Synthesis And Characterization Of Black Silicon By Silver-Assisted Chemical Etching For Solar Cell - Noor, Nur Afidah Md. (2021)
Crystalline silicon (c-Si) suffers from poor light absorption due to its indirect band gap and high reflection from its surface (about 35% in the visible region). This problem can be solved by texturing the surface of c-Si wafer to reduce its broadband reflection. Black silicon (b-Si) or nanotextured c-Si, has a huge potential for applications in solar cell due to its superior broadband light absorption within 300-1100 nm wavelength region. In this work, two-step metal-assisted chemical etching (MACE) is used to synthesize b-Si by combining low-annealing temperature of silver (Ag) film and short duration of etching of the c-Si wafer. For the b-Si fabrication, p-type (100) c-Si wafers are deposited with 15 nm Ag film using radio frequency (RF) sputtering process. Subsequently, the Ag film is annealed at low temperatures (200-230ᵒC) for 40 min in nitrogen (N2) ambient, producing Ag nanoparticles (NPs). Then, the c-Si wafers with the Ag NPs are etched in a solution containing hydrofluoric acid:hydrogen peroxide:deionized water (HF:H2O2:DI H2O) for a short duration (35-180 s). Effects of etching time, etchant volume ratio and annealing temperature towards surface morphological and optical properties by using atomic force microscope (AFM), field emission scanning electron microscope (FESEM) and UV-Vis-NIR (within 300-1100 nm wavelength region) of b-Si are then investigated. From the investigation, the b-Si with the lowest broadband reflection is produced by annealing at 230ᵒC for 40 min and etched for 70 s using HF:H2O2:DI H2O (1:5:10 by volume).